Efecto de varios agentes, a diferentes niveles de pH, sobre la tasa de filtración de la piangua, Anadara tuberculosa (Mollusca: Arcidae) - Wong, Eric; González, María Isabel; Antillón, Florencia; Glenn, Eduardo (Revista de Biología Tropical, 1997)
The effect of lemon juice, lactíc acid, acetic acid and a citric seed extract, at different pH levels, on the filtration rate of the "piangua" (Anadara tuberculosa) was studied. The study is particularly important because it can be helpful to establish the conditions to be used for depuration systems based on Ihe use of acid compounds. Specimens with diameters ranging from 4.0 to 4.5 cm, were collected from a harvester at the estuary of Puntarenas, Gulf of Nicoya. Bottles containing 1 I of saline solution (25g!l) were prepared in triplicates, adjusting the pH to 4.5, 5.0, 5.5, or 6.0 with each one of the following acids: lemon juice(Citrus aurantifolia), acetic acid (4% VIV), lactic acid (85%VIV) and CITREX (a commercial extract of citric seeds). Each bottle has oxygenated to saturation and held at room temperature. Also in triplicates, control essays were performed at pH 7.0. One animal was added to each bottle, and the filtratíon rate was determined every 8 hr for 48 hr. Citrex caused the death after 10 minutes of exposure. A neutralization of Ihe initial pH levels was found for the different treatments, slowest for acetic acid, followed by lactic acid and lemon juice. No significant difference was found between filtration rates in presence of the acid compounds and the filtration rate of the control assay. The tendency found for the filtration rate was a cyclic, non decreasing, normal one, showing that the acid compounds, in the range of the observed pH values, caused no affection on the animals' metabolismo